Influence of the free surface on hydrodynamics in a bubble column. (November 2020) - Masterov, M.V.; Baltussen, M.W.; Kuipers, J.A.M.
Highlights: Simulations of a large scale bubble column with a Direct Simulation Monte Carlo method. The method is combined with a Volume of Fluid method to represent the free surface. The presence of the interface significantly reduces the void fraction in the bubble column. The interface increases the number of small-scale eddies in the bulk. Abstract: In this paper, the influence of the free surface on hydrodynamics is investigated numerically for a pilot-scale bubble column. The free surface is modelled by means of the Volume of Fluid method (VOF), whereas the gas entities are represented by means of the Direct Simulation Monte Carlo (DSMC) method. The VOF method is parallelized using MPI and incorporated in already parallel in-house numerical code for DSMC, FoxBerry . The results obtained with the modeled free surface are compared with the reference simulation, in which the free surface is mimicked using the outlet slits, placed at the top of the column. The results show a significant impact of the free surface on generation of the small-scale eddies. Moreover, the presence of the free surface reduces the gas-holdup in the domain.